Changes in Childhood Immunizations and Intermittent Preventive Malaria Treatment in a Peripheral, Referral Immunization Center During the First 12 Months of COVID-19 Pandemic in Sierra Leone, Western Africa - Mariani, Francesco; Valentini, Piero; Yamba, Matilda; Turay, Abubakar Sidique; Bulubisi, Hazel; Moscato, Umberto; Raffaelli, Francesca; Iodice, Francesco; Buonsenso, Danilo (Frontiers in Pediatrics, 2022)
Background There is increasing evidence that the COVID-19 pandemic disrupted childhood immunization services. However, detailed reports on immunizations and preventive antimalarial prophylactic treatments delivered and how the trends changed in referral centers in low-income countries are still missing. Methods We performed a retrospective cross-sectional study. Data for vaccinations administered to children <5 years of age, according to the local vaccination schedule, were extracted from the official records of the Kent Community Health Post, Sierra Leone, in the period between April 2019 and March 2021. We compared the vaccinations performed in the first year, considered as a pre-Covid period, with the second year, post-Covid period. Both the period was then divided in four trimester each and the same analysis was operated for each trimester. A Chi-square goodness of fit test was performed to compare the number of vaccinations performed both in the two years and in the 8 trimesters. Findings 7283 vaccinations were administered: 4641 in the period between April 2019 and March 2020 and 2642 between April 2020 and March 2021. The drop in immunizations performed began as soon as the first cases were described in China. The drops were statistically significant when the first three trimesters of the two study periods were compared, while no statistically significant differences were observed for all the vaccines performed in the 4th trimesters. Vaccines administered at birth (BGC) were less affected compared to booster vaccinations. Conclusions Immunizations administered in a referral health center in Sierra Leone significantly declined during the pandemic. Although the decline was less pronounced in the last months of the pandemic, we don’t think that the small increase would indicate the recovery of previously missed vaccinations. These findings open new public health challenges for the coming years.